If it's not what You are looking for type in the equation solver your own equation and let us solve it.
39-5m=-6(5m+6)
We move all terms to the left:
39-5m-(-6(5m+6))=0
We calculate terms in parentheses: -(-6(5m+6)), so:We get rid of parentheses
-6(5m+6)
We multiply parentheses
-30m-36
Back to the equation:
-(-30m-36)
-5m+30m+36+39=0
We add all the numbers together, and all the variables
25m+75=0
We move all terms containing m to the left, all other terms to the right
25m=-75
m=-75/25
m=-3
| 4-2/3k=-11 | | y+13=5 | | -1k=23 | | -n/5=-14 | | 38r=369 | | 8(2x+8x)+5x=16-5x | | 5(3w-4)=3(3+2) | | -7y+y(3+2)=28 | | +y+5(y+1)=63-y | | 20+3y-2=13y-14-2y | | 30+45x=300 | | 36=2l+2(9) | | X2-y2=28 | | X^4-6X^2+k=0 | | 4x=7=3 | | 55+55+x+x=360 | | m+4=21 | | y/2+5=-15 | | 4(x-5)(x-3)=0 | | 6(p-6)=4(2p-3) | | -6m+1=28 | | 2/5r=2/3 | | 6(p-6)=4 | | X=4(-x+5)=10 | | -12-2x=3x | | 5m+7=7m-3 | | 3(x+5)^2=36 | | 50-(2*30d)=40-(1.5*30d) | | 82+82+x+x=360 | | 12g=12(2/3g-1 | | 2(4a+4)=a+1 | | 2x=10=-8 |